The Official Bosnian Language at the Beginning of Public Schooling in B&H: Bosniakdom and the Bosnian Language in the Textbooks of Bosnian Franciscans Ambroža Matić and Augustin Miletić - Jasmin Hodžić (Bosniaca, 2022)
Based on the available archival material and additional literature, this paper approaches the analysis of the textbooks of the Bosnian Franciscans Ambroža Matić and Augustin Miletić from the sociolinguistic aspect in the context of language naming and linguistic identity. The textbooks serve as examples from the corpus of our initial textbook literature referring to the early period or the very beginning of the contemporary (more modern) type of public schooling in Bosnia and Herzegovina, with the aim of looking at identitarian language issues closely related to the issue of national identity. The starting point is the curriculum of the state (Franciscan) primary school in Tolisa (Orašje) from 1823, on the basis of which we can speak of a significant jubilee that today marks two centuries of a particularly important tradition: the official Bosnian language at the beginning (in the early period) of modern public schooling in Bosnia and Herzegovina. Furthermore, the paper shall analyze textbooks from the beginning of the 19th century, at a time when the processes of nationalization and significant mutual identitarian alienation of the local population had not yet taken root.